Model - Model Pembelajaran pada Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) STAIN Samarinda - Syeh Hawib Hamzah (FENOMENA, 2014)
The model of learning is a vital thing in education. A good appropriate model of learning could reach the goal of learning efficently and effectively. The lecturers of education and teacher training program of STAIN Samarinda implement a various teaching and learning models when they perform their teaching, such as: model of contectual teaching, social interaction, informational proces, personal-based learning, behaviorism, cooperative learning, and problem-based learning.